Validating the Gedex HD-AGG™ Airborne Gravity Gradiometer. Issue 1 (1st December 2018) - Hatch, David; Wong, Hong; Annecchione, Maria; Hefford, Shane
Abstract : The Gedex High-Definition Airborne Gravity Gradiometer (HD-AGG ™ ) was designed and developed to deliver measurements of the gravitational field with improved signal-to-noise and resolution. The system has been under development for more than 10 years and has reached the point of commercial deployment. Knowledge of the gradiometer components being measured, noise character and resolution of the system will allow end-users to select exploration targets and determine survey parameters appropriately. The validation of the Gedex system has been progressive in nature consisting of laboratory tests and flight tests in a Cessna Caravan. The lab experiments consisted of static tests to establish the quiescent noise floor, signal confirmation tests and dynamic testing on a 6 degree-of-freedom shaker. The airborne testing included high altitude flights to confirm the noise level and character of the system over long periods. Low-level repeat surveys were carried out to establish the noise levels under survey conditions. High resolution terrain data were used to confirm the resolution of the system. Datasets from our validation program and the path forward are discussed.